The determinants and coordination of the message conveyed through the media by the Polish presidency of the Council of the European Union in 2011 – a political science approach - Tomaszyk, Mikołaj J. (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
Although Poland’s presidency of the Council of the European Union concluded almost two years ago, this period of Poland coordinating the work of one of the most significant EU institutions is still the subject of interdisciplinary studies that contribute to the assessment of the new, Lisbon model of European leadership. The paper discusses how the Polish government formulated its communication goals when beginning to prepare for the presidency. How did it define the political message of the presidency? How did it involve citizens in the activities undertaken by the Polish presidency of the EU Council? What domestic and European factors impacted on the evolution of the message of the presidency? How did the priorities of the presidency determine its communication goals? How did this message evolve on account of numerous factors?